Knockout of macrophage Zfp260 attenuates periodontitis in mice via inhibiting M1-type polarization - XIONG Jin; WANG Zuolin (Kouqiang hemian waike zazhi)
[Objective:] To explore the effect of zinc finger protein 260 (Zfp260/ZNF260) on macrophage polarization and alveolar bone resorption due to periodontitis. [Methods:] Real-time quantitative polymerase chain reaction (RT-qPCR) was used to detect the expression of ZNF260/Zfp260 in inflammatory periodontal tissues of human/wild-type mice. The expression of Zfp260 in RAW264.7 cells in inflammatory or non-inflammatory environments was detected by RT-qPCR. Mice with specific knockout of Zfp260 were bred, and control mice (Zfp260f/f; Lyz2-cre-) and conditional knockout (cKO) mice (Zfp260f/f; Lyz2-cre+) periodontitis models were established respectively. Morphological changes of alveolar bone were detected by micro-CT and hematoxylin-eosin (HE) staining. The polarization of RAW264.7 cells when Zfp260 was knocked down via specific small interfering RNA (siRNA) in an inflammatory environment was detected by RT-qPCR and western blotting. RT-qPCR and immunofluorescence staining were used to observe the expression of M1 and M2 macrophage-associated markers in periodontal tissues. [Results:] The expression of ZNF260/Zfp260 in inflammatory periodontal tissues of human/wild-type mice were significantly higher than that of healthy periodontal tissues. The expression of Zfp260 in RAW264.7 cells was significantly increased in an inflammatory environment. Alveolar bone resorption in the ligatured side of cKO mice was significantly less than that of flox/flox mice. The knockdown of Zfp260 in RAW264.7 cells could inhibit its M1 polarization in an inflammatory environment. The expression of M1-related markers in inflammatory periodontal tissues was significantly lower than that of flox/flox mice. [Conclusion:] Inhibition of Zfp260 in macrophage decreased M1 polarization and rescued the bone loss due to periodontitis.